(untitled) (SAARC Journal of Agriculture, 2021)
An experiment was conducted to evaluate the yield performance of potato varieties with chemical and organic fertilizer at Chilime, Rasuwa. The experiment consisted of eight treatment combinations laid out in two factors Randomized Complete Block Design (RCBD) with three replications. Four potato varieties (Khumal-Seto-1, Khumal-Ujjwal, Janak-Dev and Kufri-Jyoti) with fertilizer (Recommended dose of chemical fertilizer (100:100:60 NPK kg ha-1) and organic farmyard manure (15 mt ha-1) were used to make eight treatment combinations. The results showed that Janak-Dev had the highest plant height (69.3 cm) and canopy diameter (60.92 cm). Khumal-Seto-1 had highest number of main stems per hill (3.75) which were statistically similar to Kufri-Jyoti (3.42) and Khumal-Ujjwal (3.25). Janak-Dev had the lowest number of main stems per hill (1.87). The effect of fertilizer was nonsignificant. Flowering occurred earlier in Janak-Dev at 61.17 days after sowing while Kufri-Jyoti flowered after 73.17 days after sowing. The highest number of tubers were found in Khumal-Seto-1 (9.167) and lowest in Janak-Dev (5.750). Number of tubers per plant was not affected by types of fertilizers used. Maximum weight of each tuber (107.7 grams), yield per plant (780 grams) and yield per hectare (37.1 mt ha-1) were obtained from Kufri-Jyoti. These parameters were the highest from chemical fertilizer application. This field experiment showed that Kufri-Jyoti with recommended dose of chemical fertilizer was appropriate to get optimum yield under Chilime condition. SAARC J. Agric., 19(1): 103-112 (2021)